Factores personales y de acceso que inciden sobre la permanencia y deserción universitaria en estudiantes de pedagogía en una universidad chilena de zona geográfica extrema - Gonzalez Sanzana, Alvaro; Renato Arce Secul (My University, 2021)
This study examines the phenomenon of university retention and dropout in pre-service teachers at the University of Magallanes, for the 2010 to 2019 cohorts, through some of its incidence factors, both in relation to variables linked to the previous school career of the students, as well as socio-demographic. To this end, the results of 705 pre-service teachers from 2010 to 2019 are analyzed through official data provided by the institution. The results of the study show that the academic indicator prior to the university stage that most affects the university retention and dropout of students is the high school grade point average. The score obtained by students in the University Selection Test, however, has no incidence on this phenomenon. On the other hand, women achieve significantly higher retention rates than men, and students who enter through special access to prepare for the Pedagogies present similar indicators to those entered through the PSU. The results invite to continue deepening in access ways to study Pedagogy that privilege the school academic path over a selection test, as well as special preparation programs during secondary education for these careers.
Keywords: Dropout (neural networks)